EFFECT OF CHEMICAL ADDITIVES THAT SLOW THE SOLIDIZING TIME ON THE PROPERTIES OF PORTLAND CEMENT (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this article was studied the physical and mechanical properties of concrete with superplasticizers of Sikament RMC-519 and Sika Retarder, as well as the results of laboratory studies were given in the form of the table and graphs.